Oxygen-enhanced MRI and radiotherapy in patients with oropharyngeal squamous cell carcinoma. (March 2023) - Bluemke, Emma; Bertrand, Ambre; Chu, Kwun-Ye; Syed, Nigar; Murchison, Andrew G.; Cooke, Rosie; Greenhalgh, Tessa; Burns, Brian; Craig, Martin; Taylor, Nia; Shah, Ketan; Gleeson, Fergus; et al.
Highlights: Assessed oxygen-enhanced MRI in patients having radiotherapy for head and neck cancer. We report how native R1 and OE-MRI response relates to patient outcome. We report how changes in R1 before and after radiotherapy related to clinical outcome. Results were consistent with OE-MRI theory and previously reported tumour responses. There is important work to be done to improve robustness of OE-MRI technique in humans. Abstract: Background and purpose: This study aimed to assess the role of T1 mapping and oxygen-enhanced MRI in patients undergoing radical dose radiotherapy for HPV positive oropharyngeal cancer, which has not yet been examined in an OE-MRI study. Materials and methods: Variable Flip Angle T1 maps were acquired on a 3T MRI scanner while patients (n = 12) breathed air and/or 100 % oxygen, before and after fraction 10 of the planned 30 fractions of chemoradiotherapy ('visit 1' and 'visit 2', respectively). The analysis aimed to assess to what extent (1) native R1 relates to patient outcome; (2) OE-MRI response relates to patient outcome; (3) changes in mean R1 before and after radiotherapy related to clinical outcome in patients with oropharyngeal squamous cell carcinoma. Results: Due to the radiotherapy being largely successful, the sample sizes of non-responder groups were small, and therefore it was not possible to properly assess the predictive nature of OE-MRI. The tumour R1 increased in some patients while decreasing in others, in a pattern that was overall consistent with the underlying OE-MRI theory and previously reported tumour OE-MRI responses. In addition, we discuss some practical challenges faced when integrating this technique into a clinical trial, with the aim that sharing this is helpful to researchers planning to use OE-MRI in future clinical studies. Conclusion: Altogether, these results suggest that further clinical OE-MRI studies to assess hypoxia and radiotherapy response are worth pursuing, and that there is important work to be done to improve the robustness of the OE-MRI technique in human applications in order for it to be useful as a widespread clinical technique.